2022
DOI: 10.3390/ijms23179773
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A in Human Liver: Significant Source of Inflammation and Trigger of Liver Fibrosis Initiation

Abstract: IL-17A is considered to guide liver inflammation and fibrosis. From twenty-two human liver samples of different fibrosis stages (F0 to F4), IL-17A, IL-22, and TGFβ1 protein expression in liver tissue lysates were analyzed. Ten paired samples of liver tissue (F0–F1 stage) and blood from the same patient were used to analyze intrahepatic and blood T-lymphoid IL-17A+ cells by flow cytometry. The analyses have been performed regardless of pathology, considering the stage of fibrosis. Human liver tissue was used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Ghazavi et al found the same with a significant difference [26]. Indeed, Th17 cells are the main source of IL-17 production which stimulates the secretion of IL-8, which is a potent chemoattractant of neutrophils involved in conditions such as COVID-19 [27,28].…”
Section: Discussionmentioning
confidence: 89%
“…Ghazavi et al found the same with a significant difference [26]. Indeed, Th17 cells are the main source of IL-17 production which stimulates the secretion of IL-8, which is a potent chemoattractant of neutrophils involved in conditions such as COVID-19 [27,28].…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, correlation analysis of KEGG demonstrated significant enrichment of multiple autoimmune disease-related pathways such as rheumatoid arthritis, asthma, inflammatory bowel disease, and Th17 cell differentiation. Th17 cell differentiation pathway has been closely related to hepatitis, fibrosis, and autoimmune diseases ( Beringer and Miossec, 2018 ; Kartasheva-Ebertz et al., 2022 ). Therefore, these findings explain the “hygiene hypothesis” to some extent, but further in-depth research is necessary ( Bach, 2017 ; Caraballo, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Th17 and mucosal-associated invariant T (MAIT) cells in the liver secreted IL-17 A, which triggered fibrosis via inducing the expression of IL-6 and other pro-fibrotic markers thus suggesting that IL-17A could be a target for anti-fibrotic treatment ( 41 ). Both IL-17A and Th17 related cytokines including IL-6 and TGF-β1 participated in the progress of liver cirrhosis.…”
Section: Novel Advances Targeting Immune Factorsmentioning
confidence: 99%